2016
DOI: 10.1016/j.fuel.2016.06.073
|View full text |Cite
|
Sign up to set email alerts
|

Lift-off and blow-off of methane and propane subsonic vertical jet flames, with and without diluent air

Abstract: The paper seeks to increase understanding of subsonic jet flame blow-off phenomena, through experimental studies that include the controlled introduction of air into the fuel jet. As the molar concentration of air in the jet flame gas, Aj, is increased the reaction zone becomes leaner, and the flame lift-off distance increases.Eventually, flame oscillations develop and are followed by flame blow-off. A jet mixing analysis enables the extent of the leaning-off of the mixture to be estimated. From this, the redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…6 Details of how a blow-off develops were studied experimentally by AP at the State Key Laboratory in Fire Science, Hefei. Subsonic jet flames of methane and propane were employed, with pipe diameters ranging between 3 and 8 mm, as described in [4]. Fig.…”
Section: Lift-off Distance Subsonic and Choked Blow-offmentioning
confidence: 99%
See 3 more Smart Citations
“…6 Details of how a blow-off develops were studied experimentally by AP at the State Key Laboratory in Fire Science, Hefei. Subsonic jet flames of methane and propane were employed, with pipe diameters ranging between 3 and 8 mm, as described in [4]. Fig.…”
Section: Lift-off Distance Subsonic and Choked Blow-offmentioning
confidence: 99%
“…This was conducted at the State Key Laboratory of Fire Science, Hefei, described in [4], and at the Centre for Technological Risk Studies at the Polytechnic University of Catalonia, Barcelona, described in [28]. These data are also shown on this figure.…”
Section: Values Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study indicated that the liftoff length is sensitive to exit velocity and exit diameter. 19 As the velocity increases, the intense mixing of ambient air and fuel will generate a higher strain rate in which eventually would lead to the flame quenching. The computation work shows that the smaller exit diameter gives better conditions for earlier flame blow off.…”
Section: Flame Liftoffmentioning
confidence: 99%